1972
DOI: 10.2307/1934237
|View full text |Cite
|
Sign up to set email alerts
|

Relationships between Cell‐Wall Fractions, Nitrogen, and Standing Crop in Aquatic Macrophytes

Abstract: Shoot samples of 21 species of aquatic macrophytes were separated into cell—wall and noncell—wall fractions by digestion in a neutral—detergent solution. This method is useful for estimating the digestibility of plant production by native herbivores. Nitrogen content was also used as an indication of nutritive quality. Amounts of noncell—wall material and nitrogen in the dry matter decreased as shoot standing crops of the different species increased.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
15
0

Year Published

1981
1981
1995
1995

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(18 citation statements)
references
References 22 publications
3
15
0
Order By: Relevance
“…The order of decrease in mean annual concentration of nutrients were Ca > N > K > Mg > Na > P. The absorption of calcium in relation to potassium was like many other floating and submerged plants (Straskraba, 1968). Concentrations of calcium and magnesium were high and of phosphorus, potassium and sodium low as compared to the report of Boyd (1970) and Polisini & Boyd (1972), indicating a considerable amount of 'luxury consumption' (Gerloff, 1973).…”
Section: Discussionmentioning
confidence: 55%
“…The order of decrease in mean annual concentration of nutrients were Ca > N > K > Mg > Na > P. The absorption of calcium in relation to potassium was like many other floating and submerged plants (Straskraba, 1968). Concentrations of calcium and magnesium were high and of phosphorus, potassium and sodium low as compared to the report of Boyd (1970) and Polisini & Boyd (1972), indicating a considerable amount of 'luxury consumption' (Gerloff, 1973).…”
Section: Discussionmentioning
confidence: 55%
“…It has been suggested that this pattern may result from differential rates of decomposition of different fractions (Visser 1964 ;Planter 1970 ;Boyd 1970Boyd , 1971Kaushik & Hynes 1971 ;Wetzel & Manny 1972) . Since the diphasic pattern seems to be particularly well developed in emergent and floating macrophytes (Boyd 1970(Boyd , 1971Mason & Bryant 1975 ;Howard-Williams & Junk 1976 ;Howard Williams & Howard-Williams 1978) it is probably partly related to the greater development of supporting and conducting tissue in these species (Polisini & Boyd 1972 ;HowardWilliams & Junk 1977) . Cynodon dactylon falls into this category, having stiff erect shoots bearing rather softer leaves .…”
Section: Discussionmentioning
confidence: 99%
“…Because duckweed is only capable of spreading growth, there is no need for more supportive tissue at high densities. Polisini & Boyd (1972) measured standing crops and noncellwall fraction for 16 aquatic macrophytes and found the proportion of cell-wall material (00-noncellwall fraction) increased as standing crop increased. Results of the present research indicate that this trend is also interspecific, at least for plants with certain growth habits.…”
Section: Resultsmentioning
confidence: 99%